Renal Inpatient Nutrition Screening Tool (Renal iNUT) – A validity and reliability assesment for Turkey - Coşkun, Ayfer Beyaz; Elibol, Emine; Genç, Fatih; Erdoğan, Esin (ARAN Ediciones S.L, 2025)
Background and aims: there is a need for a kidney-specific nutritional screening tool for patients with renal failure. It was planned to perform the validity and reliability of the Renal Inpatient Nutrition Screening Tool screening tool developed for renal patients in Turkey. Methods: the validity and reliability of the Renal Inpatient Nutrition Screening Tool were investigated by comparing it with the Malnutrition Universal Screening Tool and the Subjective Global Assessment for assessing malnutrition in 153 adult patients newly admitted to the nephrology unit. Nutritional status was assessed using anthropometric measurements and nurse opinion was assessed using a questionnaire. Results: the Renal Inpatient Nutrition Screening Tool was found to be more sensitive than the Malnutrition Universal Screening Tool in identifying increased malnutrition risks and providing dietary guidance. Cramer V coefficient was 0.238 between the Malnutrition Universal Screening Tool and the Renal Inpatient Nutrition Screening Tool, and 0.137 between the Subjective Global Assessment and the Renal Inpatient Nutrition Screening Tool, indicating the compatibility of the Renal Inpatient Nutrition Screening Tool with the variables in the Malnutrition Universal Screening Tool screening tool. A significant positive moderate correlation was observed between the total number of red boxes in the Renal Inpatient Nutrition Screening Tool and the total score of Malnutrition Universal Screening Tool (p < 0.05; r = 0.404). Conclusions: the Renal Inpatient Nutrition Screening Tool is a valid and reliable tool for assessing malnutrition risks in renal patients in Turkey, particularly when used by experienced specialist nurses in nephrology units. © 2025 SENPE y and Arán Ediciones S.L.
Herramienta de detección nutricional para pacientes hospitalizados con insuficiencia renal (Renal iNUT): evaluación de la validez y fiabilidad en Turquía
Keywords: Malnutrition; Malnutrition Universal Screening Tool; Nephrology; Renal Inpatient Nutrition Screening Tool; Subjective Global Assessment